A method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag
Patent Information
- Application Number
- CN202310544788.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-05-15
AI Technical Summary
然而,目前煤气化渣的处理方法是填埋,这不仅造成了碳资源的巨大浪费,而且还造成了土地占用和环境污染
(1)为解决煤气化渣大量排放带来的资源浪费、土地占用、环境污染等问题提供一条新的途径;
Smart Images

Figure CN116574910B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallurgical technology, specifically to a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag. Background Technology
[0002] Coal chemical industry refers to the industry that uses coal as raw material and processes it chemically to convert it into gaseous, liquid, and solid fuels and chemicals. Based on different production processes and products, it is mainly divided into three product chains: coal coking, coal gasification, and coal liquefaction. Coal gasification plays a particularly important role in coal chemical industry, mainly used to produce city gas, various industrial fuel gases, and syngas. However, while the coal chemical industry is booming, it also generates a large amount of solid waste: coal gasification slag.
[0003] Coal gasification slag includes coarse slag and fine slag. Coarse slag is the water-containing slag discharged from the bottom ash lock hopper of the gasifier after the slurry coal particles have undergone melting, quenching, and condensation processes under high temperature and pressure conditions in the gasifier. The residual carbon content varies greatly depending on the type of coal, the type of gasifier, and the operating conditions of the gasifier, generally ranging from 10% to 30%. The particle size is concentrated between 16 mesh and 4 mesh, and it accounts for about 80% of the total gasification slag discharge. Fine slag is the water-containing slag carried out by the crude coal gas flow from the top of the gasifier and obtained after preliminary washing, purification, and sedimentation. It has a higher residual carbon content, generally exceeding 30%, and the particle size is less than 16 mesh, with about one-third being less than 200 mesh. It accounts for about 20% of the total gasification slag discharge. Both coarse and fine coal gasification slag contain abundant silica, alumina, and iron oxide, with the combined content of these three components reaching up to 70% or more, meeting the ASTM Class F fly ash standard and exhibiting a certain degree of pozzolanic activity. In addition, coal gasification slag also contains inorganic substances such as calcium oxide, magnesium oxide, and titanium dioxide.
[0004] In 2020, China's coal-to-gas production reached 4.7 billion cubic meters, and the production of coal chemical liquids, olefins, and ethylene glycol was approximately 30.85 million tons. Coal consumption in the coal chemical industry increased from 117.4 million tons in 2016 to 300 million tons in 2020, and China's annual CGS production also surged to 60 million tons. However, the current method of disposing of coal gasification slag is landfilling, which not only results in a huge waste of carbon resources but also causes land occupation and environmental pollution. Due to the large volume of coal gasification slag emissions and the inadequate treatment methods, there is an urgent need to find a new method for coal gasification slag recovery. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag. The method involves uniformly mixing coarse coal gasification slag, fine coal gasification slag, and additives to form a powder, then pressing the mixture into pellets and smelting them at high temperature to prepare a ferrosilicon-aluminum-calcium alloy that can be used as a deoxidizer and alloying additive in steelmaking, as well as as an inoculant and spheroidizing agent in cast iron production.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag, comprising the following steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification into powder of a certain particle size; Step 2: Mix the crushed powder with the additives in the specified proportions; Step 3: Press the mixed powder into pellets; Step 4: Dry the pressed pellets at 50℃~200℃ for 12 h~48 h; Step 5: The dried pellets are smelted at a high temperature of 1200℃~2200℃ to obtain an alloy with a certain composition; Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0007] The above-mentioned method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag, wherein... In step 1, the coarse slag, medium slag, and fine slag from coal gasification are solid wastes generated by the coal gasification process in the coal chemical industry. The coarse slag is the large-particle waste slag discharged from the bottom of the gasifier during the coal gasification process. The medium slag and fine slag are the small-particle waste slags carried out of the gasifier by the coal gas flow during the coal gasification process. During the settling and collection process, they are divided into medium slag, which settles preferentially in the settling tank and has a larger particle size and lower carbon content, and fine slag, which settles more slowly in the settling tank and has a smaller particle size and higher carbon content.
[0008] In step 1, the composition of the coarse, medium, and fine coal gasification slag, by mass percentage, is as follows: C 5~60%, SiO2 30~70%, Al2O3 ≤30%, Fe2O3 ≤30%, CaO ≤30%, MgO ≤10%, Na2O ≤5%, K2O ≤5%, TiO2 ≤5%, and the content of other single metal oxides ≤1%.
[0009] In steps 1-2, the particle size of the crushed powder is less than 10 mesh.
[0010] In step 2, the additive is one or more of SiO2, Al2O3, CaO, Fe2O3, Na2CO3, NaCl, K2CO3, and NaF, which can adjust the proportion of raw material oxides and / or improve the flowability of the furnace charge.
[0011] In steps 2-3, the mass of carbon in the mixed powder accounts for 10-40% of the total mass of the mixed powder, and the mass of the additive accounts for 0.5-10% of the total mass of the mixed powder.
[0012] In step 3, the diameter of the compressed pellets is 5 mm to 100 mm, and the pressure during pellet compression is 10 MPa to 40 MPa.
[0013] In step 5, the equipment used in the high-temperature smelting process is one of the following: resistance furnace, induction furnace, and electric arc furnace.
[0014] In step 5, the mass of silicon, aluminum, and calcium in the alloy shall not be less than 60% of the total mass of the alloy.
[0015] Compared with the prior art, the advantages of the present invention are: (1) To provide a new way to solve the problems of resource waste, land occupation and environmental pollution caused by the large-scale discharge of coal gasification slag; (2) Improve the recovery rate and economic added value of coal gasification slag, make full use of the residual carbon and valuable metals such as silicon, iron, aluminum and calcium in the coal gasification slag, reduce resource waste, turn waste into treasure, and realize the recycling of resources; (3) Promote the sustainable development of the coal chemical industry and extend the coal industry chain; (4) Compared with the traditional carbothermal reduction method for producing alloys such as ferrosilicon, this method has a simpler process and lower raw material costs, which can effectively reduce production costs; (5) Using coal gasification slag as raw material to prepare ferrosilicon aluminum calcium alloy, no additional carbonaceous reducing agent is required, realizing the recycling of all components of coal gasification slag and saving resources. Attached Figure Description
[0016] Figure 1 This is a process flow diagram of a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag. Detailed Implementation
[0017] Example 1 like Figure 1 As shown, a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag includes the following specific steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification to a particle size of less than 10 mesh.
[0018] Step 2: Mix the crushed powder with the additive in a certain proportion; the additive is a mixture of SiO2 and NaCl in a mass ratio of 1:1; the mass of carbon accounts for 20% of the total mass of the mixed powder, and the mass of the additive accounts for 5% of the total mass of the mixed powder.
[0019] Step 3: Press the mixed powder into pellets with a diameter of 50 mm at a pressure of 10 MPa.
[0020] Step 4: Dry the pressed pellets at 150℃ for 12 h.
[0021] Step 5: Melt the pellets at 1800℃ in a resistance furnace to obtain an alloy with a certain composition.
[0022] Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0023] In this Example 1, the obtained silicon-iron-aluminum-calcium alloy product is a silvery-white block with a metallic luster; the microstructure contains separate silicon phase and silicon-iron-aluminum-calcium alloy phase; in the composition of the alloy, silicon, aluminum and calcium account for 67.43% of the total mass.
[0024] Example 2 like Figure 1 As shown, a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag includes the following specific steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification to a particle size of less than 10 mesh.
[0025] Step 2: Mix the crushed powder with the additive in a certain proportion; the additive is a mixture of Al2O3 and NaF in a mass ratio of 1:1; the mass of carbon accounts for 25% of the total mass of the mixed powder, and the mass of the additive accounts for 5% of the total mass of the mixed powder.
[0026] Step 3: Press the mixed powder into pellets with a diameter of 50 mm at a pressure of 20 MPa.
[0027] Step 4: Dry the pressed pellets at 150℃ for 24 hours.
[0028] Step 5: Melt the pellets at 1800℃ using an induction furnace to obtain an alloy with a certain composition.
[0029] Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0030] In this Example 2, the obtained silicon-iron-aluminum-calcium alloy product is a silvery-white block with a metallic luster; the microstructure contains separate silicon phase and silicon-iron-aluminum-calcium alloy phase; in the composition of the alloy, silicon, aluminum and calcium account for 70.35% of the total mass.
[0031] Example 3 like Figure 1 As shown, a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag includes the following specific steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification to a powder particle size of less than 40 mesh.
[0032] Step 2: Mix the crushed powder with the additive in a certain proportion; the additive is a mixture of Al2O3, SiO2 and NaF in a mass ratio of 1:1:1; the mass of carbon accounts for 27% of the total mass of the mixed powder, and the mass of the additive accounts for 5% of the total mass of the mixed powder.
[0033] Step 3: Press the mixed powder into pellets with a diameter of 50 mm at a pressure of 20 MPa.
[0034] Step 4: Dry the pressed pellets at 150℃ for 16 h.
[0035] Step 5: Melt the pellets at 2200℃ using an electric arc furnace to obtain an alloy with a certain composition.
[0036] Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0037] In this Example 3, the obtained silicon-iron-aluminum-calcium alloy product is a silvery-white block with a metallic luster; the microstructure contains separate silicon phase and silicon-iron-aluminum-calcium alloy phase; in the composition of the alloy, silicon, aluminum and calcium account for 75.25% of the total mass.
[0038] Example 4 like Figure 1 As shown, a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag includes the following specific steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification to a powder particle size of less than 40 mesh.
[0039] Step 2: Mix the crushed powder with the additive in a certain proportion; the additive is a mixture of Al2O3, CaO and NaF in a mass ratio of 1:1:1; the mass of carbon accounts for 30% of the total mass of the mixed powder, and the mass of the additive accounts for 5% of the total mass of the mixed powder.
[0040] Step 3: Press the mixed powder into pellets with a diameter of 50 mm at a pressure of 20 MPa.
[0041] Step 4: Dry the pressed pellets at 150℃ for 24 hours.
[0042] Step 5: Melt the pellets at 1800℃ using an induction furnace to obtain an alloy with a certain composition.
[0043] Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0044] In this Example 4, the obtained silicon-iron-aluminum-calcium alloy product is a silvery-white block with a metallic luster; the microstructure contains separate silicon phase and silicon-iron-aluminum-calcium alloy phase; in the composition of the alloy, silicon, aluminum and calcium account for 60.23% of the total mass.
[0045] Example 5 like Figure 1 As shown, a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag includes the following specific steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification to a powder particle size of less than 100 mesh.
[0046] Step 2: Mix the crushed powder with the additive in a certain proportion; the additive is a mixture of Al2O3 and Na2CO3 in a mass ratio of 1:1; the mass of carbon accounts for 18% of the total mass of the mixed powder, and the mass of the additive accounts for 5% of the total mass of the mixed powder.
[0047] Step 3: Press the mixed powder into pellets with a diameter of 50 mm at a pressure of 10 MPa.
[0048] Step 4: Dry the pressed pellets at 150℃ for 24 hours.
[0049] Step 5: Melt the pellets at 1600℃ in a resistance furnace to obtain an alloy with a certain composition.
[0050] Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0051] In this Example 5, the obtained silicon-iron-aluminum-calcium alloy product is a silvery-white block with a metallic luster; the microstructure contains separate silicon phase and silicon-iron-aluminum-calcium alloy phase; in the composition of the alloy, silicon, aluminum and calcium account for 60.87% of the total mass.
[0052] Example 6 like Figure 1 As shown, a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag includes the following specific steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification to a powder particle size of less than 100 mesh.
[0053] Step 2: Mix the crushed powder with the additive in a certain proportion; the additive is Na2CO3 powder; the mass of carbon accounts for 20% of the total mass of the mixed powder, and the mass of the additive accounts for 5% of the total mass of the mixed powder.
[0054] Step 3: Press the mixed powder into pellets with a diameter of 50 mm at a pressure of 10 MPa.
[0055] Step 4: Dry the pressed pellets at 150℃ for 18 hours.
[0056] Step 5: Melt the pellets at 1900℃ using an induction furnace to obtain an alloy with a certain composition.
[0057] Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0058] In this Example 6, the obtained silicon-iron-aluminum-calcium alloy product is a silvery-white block with a metallic luster; the microstructure contains separate silicon phase and silicon-iron-aluminum-calcium alloy phase; in the composition of the alloy, silicon, aluminum and calcium account for 68.74% of the total mass.
[0059] Example 7 like Figure 1 As shown, a method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag includes the following specific steps: Step 1: Crush the coarse slag, medium slag, and fine slag from coal gasification to a powder particle size of less than 50 mesh.
[0060] Step 2: Mix the crushed powder with the additive in a certain proportion; the additive is NaF powder; the mass of carbon accounts for 20% of the total mass of the mixed powder, and the mass of the additive accounts for 5% of the total mass of the mixed powder.
[0061] Step 3: Press the mixed powder into pellets with a diameter of 50 mm at a pressure of 10 MPa.
[0062] Step 4: Dry the pressed pellets at 150℃ for 18 hours.
[0063] Step 5: Melt the pellets at 2100℃ using an electric arc furnace to obtain an alloy with a certain composition.
[0064] Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy.
[0065] In this embodiment 7, the obtained silicon-iron-aluminum-calcium alloy product is a silvery-white block with a metallic luster; the microstructure contains separate silicon phase and silicon-iron-aluminum-calcium alloy phase; in the composition of the alloy, silicon, aluminum and calcium account for 75.42% of the total mass.
Claims
1. A method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag, characterized in that... Follow these steps: Step 1: Crush the coarse slag, intermediate slag, and fine slag from coal gasification into powder; wherein the composition of the coarse slag, intermediate slag, and fine slag, by mass percentage, is: C 5~60%, SiO2 30~70%, Al2O3 ≤30%, Fe2O3 ≤30%, CaO ≤30%, MgO ≤10%, Na2O ≤5%, K2O ≤5%, TiO2 ≤5%, and the content of other single metal oxides ≤1%; Step 2: The crushed powder and additives are mixed in a certain proportion; the mass of carbon accounts for 10-40% of the total mass of the mixed powder, and the mass of the additives accounts for 0.5-10% of the total mass of the mixed powder; the additives are one or more of SiO2, Al2O3, CaO, Fe2O3, Na2CO3, NaCl, K2CO3 and NaF. Step 3: Press the mixed powder into pellets; Step 4: Dry the pressed pellets at 50℃~200℃ for 12h~48h; Step 5: The dried pellets are smelted at 1900℃~2200℃ to obtain an alloy, wherein the mass of silicon, aluminum and calcium in the alloy is not less than 60% of the total mass of the alloy; Step 6: After separating the alloy from the slag, it is cast to obtain a silicon-iron-aluminum-calcium alloy. The microstructure of this silicon-iron-aluminum-calcium alloy contains separate silicon phases and silicon-iron-aluminum-calcium alloy phases.
2. The method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag according to claim 1, characterized in that... In steps 1-2, the particle size of the crushed powder is less than 10 mesh.
3. The method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag according to claim 1, characterized in that... In step 3, the diameter of the compressed pellets is 50mm~100mm, and the pressure during pellet compression is 10MPa~40MPa.
4. The method for preparing ferrosilicon-aluminum-calcium alloy by high-temperature smelting of coal gasification slag according to claim 1, characterized in that... In step 5, the equipment used in the high-temperature smelting process is one of the following: resistance furnace, induction furnace, and electric arc furnace.
Citation Information
Patent Citations
Method for non-solid waste discharge of magnesium extraction tailings of serpentine
CN110904333A